Afordansi Platform, Privasi, dan Pola Komunikasi Antarpribadi: Studi tentang Pengalaman Romantis Generasi Z di MiChat - Indraswari, Ririn (Universitas Pattimura, 2025)
This study explores the interpersonal communication patterns of Generation Z in forming romantic relationships through the MiChat application in Sidrap Regency, South Sulawesi. Using a qualitative approach that combines surveys, data analysis, and a netnographic research design, the study investigates the experiences of users aged 19–28. Particular attention is given to how platform affordances—especially location-based features—shape interactions while simultaneously raising privacy concerns. The findings reveal that Generation Z’s communication on MiChat is characterized by pragmatism, efficiency, and transactional orientation, with relatively low emotional investment. Platform architecture and the social reputation of MiChat significantly influence how users develop communication strategies, manage self-presentation, and negotiate privacy boundaries. Unlike other dating applications, MiChat fosters a distinct communication ecosystem where users adapt interaction patterns to balance relational opportunities with social and personal risks. The novelty of this research lies in demonstrating how technological affordances and privacy issues simultaneously shape romantic communication practices in a socially stigmatized digital space. This study contributes to the fields of social and political sciences by emphasizing the role of platform architecture in understanding interpersonal communication dynamics among youth. The study also recommends more sensitive policy and digital literacy approaches addressing privacy, communication ethics, and the broader social impact of location-based applications on younger generations.